Effect of basal and post-flood nitrogen fertilization on performance of rice (Oryza sativa) under conditions of intermediate deep-water and simulated flash-flooding - Sharma, A R` (The Indian Journal of Agricultural Sciences, 2012)
An experiment was conducted during rainy seasoll of 1991 and 1992 at Cuttack to study the effect of basal and top-dressing of nitrogen (0,20 and 40 kg N/ha) on growth and yield of direct-sown 'Gayatri' rice (Oryza sativa L.) under conditions of intermediate deep-water (0-50 cm) and simulated flash-flooding (submergence at 75 days after germination for 10 days). Flash-flooding decreased the tillers/m2 (18.3%). dry-matter accumulation (47.4%) and grain yield (31.3%) compared with the natural submergence of intermediate water depth. However, the adverse effect was more pronounced on plants grown without N than with 40 kg N/ha at sowing. Basal application of 40 kg N/ha increased the grainyield (+ 1.01 tonnes/ha) significantly due to better initial crop vigour, leading to higher number and weight of panicles at maturity. The beneficial effect of N fertilization was due to higher tiller survivability and dry-matter production. Top-dressing 20 kg N/ha at 85 days after germination. (after termination of flashÂ·flooding) increased the yield sigllificantly under submerged condition (+ 0.25-0.56 tonne/ha), particularly when basal N was not given, but did not prove effective under submergence-free condition. The result indicated that loss in yield due to flashÂ·flooding could be compensated partially by N fertilization at sowing and after the submergence stress.